Federalism, but how? The impact of vertical fiscal imbalance on economic growth. Evidence from Belgium. (3rd September 2021) - Mitra, Alessio; Chymis, Athanasios
Abstract: This paper applies both parametric and nonparametric synthetic control methods in the case of a specific federal reform. It evaluates the impact of Belgium's constitutional federalism reform of 1993 on GDP per capita. The findings show a negative impact of the reform on economic growth. This negative impact ceases soon after 2001, when a subsequent reform reduced the vertical fiscal imbalance that characterized the 1993 federal reform. It is argued that the presence of a strong federalism with subnational spending autonomy and, conversely, a centralized tax system, enhanced pork barrel spending, a common pool problem, thus damaging economic growth.